Microinjection Method for Analyzing Zebrafish Early Stage Oocytes - Kobayashi, Manami; Jamieson-Lucy, Allison; Mullins, Mary C. (Frontiers in Cell and Developmental Biology, 2021)
Maternal factors which accumulate and establish oocyte polarity during the early stages of oogenesis play key roles in embryonic development, as well as germ cell formation. However, vertebrate oogenesis, especially early stages of oogenesis, is not well understood due to the difficulty of accessing these oocytes and the lack of analytical methods. Here, we report on a microinjection method for analyzing zebrafish early-stage oocytes and some artifacts to be aware of when performing oocyte injections or analyzing oocytes. Using this method, we successfully injected mRNAs encoding fluorescent-tagged proteins into early-stage oocytes and observed subcellular localization in the live oocytes. This method is expected to advance the functional analysis of genes involved in oogenesis.